Salutogenic presence supports a healthpromoting work life - Vinje, Hege Forbech; Hanson Ausland, Liv (Socialmedicinsk tidskrift, 2013)
Many employees of the Norwegian municipal health services retire before reaching retirement age. In Norway, initiatives to retain health care workers are part of a broad strategy to retain older workers in all occupations and professions. The study is explorative and qualitative. It explores older workers’ (50 +) perceptions of presence and work-related well-being. Multi-stage focus groups, individual in-depth interviews, and qualitative content analyses were carried out. To promote presence, it must be understood as somewhat more than the opposite of absence. Salutogenic presence has four characteristics: Sense of usefulness; Relational quality: wanting the best for each other; Mastery; Zest for work. Experiencing and exploring the characteristics of presence in the workplace stimulate salutogenic presence and build health-promoting working life for seniors. A leader’s role is to facilitate the process and to acknowledge the characteristics.